Lodī Puṣhtānạh - Rashād, ʻAbd al-Shakūr, 1921- (Da Puṣhto Ṭolanay da khparawano, 1956)
Political history of Lodi dynasty of Afghanistan; includes biographical sketches of noted personalities of the tribe.